VD_FINDINFO HC / 2022 / 153 vom 11. Januar 2022 - VD Tribunal cantonal (2022)
SUCCESSION, CERTIFICAT D'HÉRITIER, HÉRITIER LÉGAL, TRANSACTIONACCORD, CONJOINT SURVIVANT | 559 CC, 256 al. 2 CPC (CH), 133 CDPJ